1994
DOI: 10.1055/s-2008-1071584
|View full text |Cite
|
Sign up to set email alerts
|

Seizures Induced by Physical Exercise: Report of Two Cases

Abstract: Two children with seizures induced by physical exercise are described. Epilepsy was present from early childhood (age: 4 and 5 months), but the precipitating effect of exercise became evident only later (age: 20 months and 3.5 years). Several treatment regimes were tried, but no satisfactory seizure control could be achieved. In both children no etiological factor was known. MRI, CT and repeated interictal waking and sleeping EEG recordings were normal. Hyperventilation and photostimulation had no effect on th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
17
0
2

Year Published

2005
2005
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 34 publications
(21 citation statements)
references
References 2 publications
2
17
0
2
Order By: Relevance
“…Some recent literatures suggested that exercise reduces seizure frequency or does not increase seizure frequency [15,16]. By contrast, some studies reported that exercise such as riding the bicycle, playing football, and running induced a seizure [6,[17][18][19].…”
Section: Discussionmentioning
confidence: 92%
“…Some recent literatures suggested that exercise reduces seizure frequency or does not increase seizure frequency [15,16]. By contrast, some studies reported that exercise such as riding the bicycle, playing football, and running induced a seizure [6,[17][18][19].…”
Section: Discussionmentioning
confidence: 92%
“…De manera excepcional se ha documentado que pocas personas con la enfermedad desarrollan crisis provocadas por la actividad física (84)(85)(86)(87)(88)(89)(90). Arida y colaboradores (91) relacionan la aparición de estos eventos con alteraciones homeostáticas asociadas a fatiga, estrés, hipoxia, hipoglicemia, hiperhidratación, hiponatremia o hipertermia.…”
Section: ¿Puede La Actividad Física Inducir Crisis Epilépticas?unclassified
“…23 There are also case reports of seizures induced by exercise in children. 24 Exercise is difficult for many children with epilepsy due to their motor problems and learning disabilities, but this should not preclude their attempts to participate in games and sports activities whenever possible.…”
Section: Lifestyle Changesmentioning
confidence: 99%